Comparative study of infrared Nd:YAG pulsed laser radiation on Pt thin film - Bhari, Bibi Zulaika; Ali, Ahmad Hadi; Isiyaku, Aliyu Kabiru; Ahmad, Rabiatul Adawiah (UTHM Publisher, 2017)
This paper investigated on infrared Nd:YAG pulsed laser radiation on platinum (Pt) thin films. Pt thin films were deposited on Si by DC magnetron sputtering. Then, the deposited thin films were radiated by infrared Nd:YAG pulse laser at different laser energy. The radiated thin films were analysed based on the electrical and surface morphological properties. Four-point probe measurement shows that, the lowest resistivity was recorded when the energy laser are 110-170 mJ. Surface morphology scanned by scanning electron microscope (SEM) revealed that the surface of sample with lowest resistivity after radiated with laser is smoother than the as-deposited thin films. After laser radiation, the grain sizes of thin films increases due to the grain agglomeration on the surface area.